Determining Factors of Working Capital Financing of Micro, Small, and Medium Enterprises (MSMEs) in Islamic Banking: An Empirical Evidence from Indonesia - Maudy Rizqi Maghfirlana; Sulaeman Sulaeman (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study aims to analyze empirically the determinants of the working capital financing of MSMEs under dual-banking system like Indonesia in the period January 2015 to April 2022. By using the selected variables and the time series data analysis method, namely the Error Correction Model (ECM), this study found that: (1) In the short term, the NPF variable have a significant effect on the decline in the distribution of capital working financing in Islamic banking in Indonesia; (2) In the long term, the variables of number of branch offices and ROA have a significant influence in increasing the number of working capital financing distributions for MSMEs in Islamic banking in Indonesia. Meanwhile, the inflation variable does not have an influence on the amount of Islamic banking financing distribution in Indonesia, both in the short and long term. This research is expected to contribute to policy making related to Islamic banking financing for the MSMEs sector in Indonesia.